2021
DOI: 10.15386/mpr-1843
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self-esteem on the relationship between orthodontic treatment and the oral health-related quality of life in patients after orthodontic treatment – a systematic review

Abstract: Objective. The treatment protocol in the modern health care paradigm has shifted considerably towards enhancing the quality of life in the last decade. This is particularly important in cosmetic and elective treatments, and hence the interest in oral health-related quality of life (OHRQoL) also has increased. OHRQoL always been measured by endogenous, functional, social, or psychological determinants. Self-esteem (SE) is one of the internal factors that affect the perception of malocclusion and hence OHRQoL be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Some authors [ 10 , 11 , 20 , 21 , 22 ] also concluded that patients experienced an improvement in quality of life at the end of treatment with metal brackets. As in the present study, quality of life during the active treatment period decreased significantly but temporarily [ 10 , 11 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [ 10 , 11 , 20 , 21 , 22 ] also concluded that patients experienced an improvement in quality of life at the end of treatment with metal brackets. As in the present study, quality of life during the active treatment period decreased significantly but temporarily [ 10 , 11 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral-health-related quality of life (OHRQoL) has important implications for patient dental care [ 10 ]. Several studies have analyzed the psychological and social effects of orthodontic treatments on the OHRQoL [ 11 , 12 , 13 , 14 , 15 ]. Facial aesthetics, dental aesthetics, and functional occlusion are different factors that influence the motivation of patients to undergo orthodontic treatment and, consequently, the decrease in the psychosocial problems that influence the OHRQoL [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Child Oral Health Quality of Life Questionnaire (OHRQoL) can give light on the effects of malocclusion on people's lives and the need for orthodontic treatment outside of clinical characteristics. 9 10 11 The subjective perception of oral health is a crucial indicator since it directly influences oral health behaviors. 12…”
Section: Discussionmentioning
confidence: 99%